PENGARUH FAKTOR-FAKTOR INVESTASI TERHADAP HARGA SAHAM PT ASURANSI MULTI ARTHA GUNA TBK ( PERIODE 2015-2024) - Siti Nabila Siti Nabila; Adji Widodo (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. This study aims to analyze the effect of Return on Assets (ROA) and Debt to Equity Ratio (DER) on stock prices of companies observed during the period 2015–2024. This research is motivated by the importance of financial performance in reflecting a company’s ability to generate profits and manage its capital structure, which are commonly used by investors in making investment decisions. However, stock price movements do not always align with changes in financial ratios, making further empirical investigation necessary. This study employs a quantitative approach using an associative method to examine the relationship between independent variables and the dependent variable. The data used are secondary data obtained from companies’ annual financial statements over a ten-year period. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 26, along with classical assumption tests. The results show that, partially, Return on Assets (ROA) has no significant effect on stock prices, with a t-value of 1.377 and a significance value of 0.211 greater than 0.05. Debt to Equity Ratio (DER) also has no significant effect on stock prices, with a t-value of -0.806 and a significance value of 0.447 greater than 0.05. Simultaneously, ROA and DER do not significantly affect stock prices, indicated by an F-value of 1.853 and a significance value of 0.226 greater than 0.05. The correlation coefficient (R) of0.588 indicates a moderately strong positive relationship. These findings suggest that profitability and capital structure are not the main determinants of stock price fluctuations during the study period. Keywords: Return on Assets, Debt to Equity Ratio, Stock Price